Building Peace through Social Capital: Preventing Religious Intolerance in Manggarai, Indonesia - Robertus, Mirsel; Baghi, Felix; Buru, Puplius M. (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article examines how social capital prevents and manages religious intolerance and conflicts in Manggarai, East Nusa Tenggara, Indonesia. Departing from the limited attention paid to local community practices compared to previous studies emphasizing state regulation or religious leadership, this study focuses on how bonding, bridging, and linking social capital are operationalized in everyday life. Drawing on Putnam's social capital framework and a qualitative approach, the research employed 20 in-depth interviews, four focus group discussions (FGDs), and document analysis in Ruteng (urban) and Reo (rural), with data triangulation and cross-case comparison to enhance validity. The findings show that symptoms of intolerance are relatively rare. Conflicts such as youth disputes triggered by hoaxes or contestations over places of worship are resolved peacefully through collaborative mechanisms involving religious leaders, traditional leaders, the Interreligious Harmony Forum (FKUB), youth forums, and local government. Cultural norms of kinship, inclusivity, and unity strengthen bonding capital, cross-group dialogues serve as bridging capital, while FKUB's institutional role and government–community partnerships provide linking capital. Theoretically, the study contributes by demonstrating a hybrid model of social capital in Manggarai, where cultural traditions and institutional structures reinforce one another in sustaining interfaith harmony while exposing vulnerabilities such as minority exclusion and dependence on proactive leadership. These findings enrich scholarly debates on social capital and tolerance in plural societies and offer practical recommendations for strengthening interfaith youth engagement, embedding cultural wisdom into institutional forums, and ensuring inclusive representation within FKUB to support broader national efforts.